2012
DOI: 10.1007/s00214-012-1244-5
|View full text |Cite
|
Sign up to set email alerts
|

Electron momentum spectroscopy of metal carbonyls: a reinvestigation of the role of nuclear dynamics

Abstract: The main purpose of this work is to reinvestigate the influence of nuclear dynamics in the electronic ground state of group 6 metal hexacarbonyl compounds [W(CO) 6 , Cr(CO) 6 , Mo(CO) 6 ] on electron momentum density profiles obtained from experimental orbital reconstructions employing Electron Momentum Spectroscopy. We call into question the view (Liu et al. in Chem Phys Lett 497:229, 2010) that thermally induced nuclear displacements associated with the first three triply degenerate 1T 2g , 1T 1u , and 1T 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 88 publications
(156 reference statements)
0
16
0
Order By: Relevance
“…Thus, the vibrational effects observed at p ∼ 0 may be attributed mainly to the zero point vibrations of the ν 6 and ν 7 modes. Although vibrational effects have generally been considered to be due to thermally induced nuclear motions, 31,33,[35][36][37] it can be deduced from the above discussion that this is not the case for the 2b 1 ionization process; molecular vibration plays a crucial role in the ionization process even at T = 0 K. Indeed, an additional calculation at T = 0 K has shown that difference between the 2b 1 momentum profiles for T = 0 and 298 K is negligibly small.…”
Section: B Momentum Profiles Of Ch 2 Fmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, the vibrational effects observed at p ∼ 0 may be attributed mainly to the zero point vibrations of the ν 6 and ν 7 modes. Although vibrational effects have generally been considered to be due to thermally induced nuclear motions, 31,33,[35][36][37] it can be deduced from the above discussion that this is not the case for the 2b 1 ionization process; molecular vibration plays a crucial role in the ionization process even at T = 0 K. Indeed, an additional calculation at T = 0 K has shown that difference between the 2b 1 momentum profiles for T = 0 and 298 K is negligibly small.…”
Section: B Momentum Profiles Of Ch 2 Fmentioning
confidence: 96%
“…At almost the same time, Deleuze and his coworkers have developed another method to calculate electron momentum profiles taking vibrational effects into account, which is based on the Born-Oppenheimer molecular dynamical simulations. [35][36][37] Their theoretical studies have demonstrated that vibrational effects on electron momentum profiles are appreciable for the highest-occupied molecular orbitals of metal-carbonyl molecules 35 as well as some valence orbitals of tetrahydrofuran 36 and 1-butene. 37 These two methods have opened a door to investigate the influences of vibrational motions on molecular orbitals in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic structure of tungsten hexacarbonyl, W(CO) 6 , has previously been studied by using a variety of different experimental and theoretical methods, with experiments including vacuum ultraviolet experiments in the wavelength range of 125–350 nm [ 1 5 ], and electron energy loss [ 6 – 8 ], photoelectron [ 9 10 ], photoionisation [ 11 ] and electron momentum [ 12 – 13 ] spectroscopy. In theoretical studies, Dirac-scattered-wave (DSW) calculations [ 14 ], molecular orbital energy level calculations [ 2 ], relativistic time-dependent density functional theory (TDDFT) calculations [ 15 ], and electron momentum spectroscopy calculations [ 16 ] have been carried out. Other relevant studies include DFT calculations on the structure of W(CO) 6 and its behaviour in infrared spectroscopy [ 17 ], as well as Raman [ 18 ] and infrared [ 18 20 ] spectroscopy experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Although the equilibrium geometry approximation by eq has been widely used to analyze the experimental data, recent EMS studies have shown that molecular vibration may appreciably affect the momentum profiles of polyatomic molecules. In order to take the vibrational effects into account, we have developed a theoretical method, which is referred to as the harmonic analytical quantum mechanical (HAQM) approach . Details of the approach are given elsewhere and not repeated here.…”
Section: Theoretical Calculationsmentioning
confidence: 99%